2019
DOI: 10.3758/s13428-019-01203-7
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal associations and synesthesia: Categorical perception and structure in vowel–color mappings in a large online sample

Abstract: We report associations between vowel sounds, graphemes, and colors collected online from over 1,000 Dutch speakers. We also provide open materials, including a Python implementation of the structure measure and code for a single-page web application to run simple cross-modal tasks. We also provide a full dataset of color–vowel associations from 1,164 participants, including over 200 synesthetes identified using consistency measures. Our analysis reveals salient patterns in the cross-modal associations and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…Participants were recruited via a nationally advertised crowdsourcing website about sensory perception and synaesthesia (gno.mpi.nl, [52,53]) and the institute's online recruitment system. One hundred and fifty-nine participants (109 selfreported synaesthetes) completed the online synaesthesia screening questionnaire.…”
Section: Methods Study 1: Heterogeneous Cohort Of Online Synaesthetesmentioning
confidence: 99%
“…Participants were recruited via a nationally advertised crowdsourcing website about sensory perception and synaesthesia (gno.mpi.nl, [52,53]) and the institute's online recruitment system. One hundred and fifty-nine participants (109 selfreported synaesthetes) completed the online synaesthesia screening questionnaire.…”
Section: Methods Study 1: Heterogeneous Cohort Of Online Synaesthetesmentioning
confidence: 99%
“…These included social media (e.g. Twitter, posts in synaesthesia-related Facebook groups, a Reddit 'Ask Me Anything' event in August 2016), flyers posted at Radboud University, advertising to the Russian synaesthesia community database, and recontacting consenting individuals who had previously participated in synaesthesia research through the Groot Nationaal Onderzoek (in English, 'Large National Study', http://gno.mpi.nl/tests) [26], the University of Amsterdam, or the University of Sussex. Those recruited to the genetics study directly at the University of Edinburgh were contacted through similar methods, including online advertisements, student forms and mailing lists, and recontacting previous participants.…”
Section: Methods (A) Participant Recruitmentmentioning
confidence: 99%
“…in [i]), are lighter, greener and yellower. Cuskley et al [35] replicated these findings with a large sample size, and furthermore showed that letter category (a particular vowel) is a better predictor of colour than the acoustic measures, thus also showing a role of categorical (letter) perception.…”
Section: Introductionmentioning
confidence: 82%